Indicaxanthin from Opuntia ficus-indica Fruit Ameliorates Glucose Dysmetabolism and Counteracts Insulin Resistance in High-Fat-Diet-Fed Mice - Simona Terzo; Alessandro Attanzio; Pasquale Calvi; Flavia Mulè; Luisa Tesoriere; Mario Allegra; Antonella Amato (MDPI AG, 2021)
Obesity-related dysmetabolic conditions are amongst the most common causes of death globally. Indicaxanthin, a bioavailable betalain pigment from Opuntia ficus-indica fruit, has been demonstrated to modulate redox-dependent signalling pathways, exerting significant anti-oxidative and anti-inflammatory effects in vitro and in vivo. In light of the strict interconnections between inflammation, oxidative stress and insulin resistance (IR), a nutritionally relevant dose of indicaxanthin has been evaluated in a high-fat diet (HFD) model of obesity-related IR. To this end, biochemical and histological analysis, oxidative stress and inflammation evaluations in liver and adipose tissue were carried out. Our results showed that indicaxanthin treatment significantly reduced body weight, daily food intake and visceral fat mass. Moreover, indicaxanthin administration induced remarkable, beneficial effects on HFD-induced glucose dysmetabolism, reducing fasting glycaemia and insulinaemia, improving glucose and insulin tolerance and restoring the HOMA index to physiological values. These effects were associated with a reduction in hepatic and adipose tissue oxidative stress and inflammation. A decrease in RONS, malondialdehyde and NO levels, in TNF-α, CCL-2 and F4-80 gene expression, in p65, p-JNK, COX-2 and i-NOS protein levels, in crown-like structures and hepatic inflammatory foci was, indeed, observed. The current findings encourage further clinical studies to confirm the effectiveness of indicaxanthin to prevent and treat obesity-related dysmetabolic conditions.